Corneal stromal elasticity and viscoelasticity assessed by atomic force microscopy after different cross linking protocols. (September 2015) - Dias, Janice; Diakonis, Vasilios F.; Lorenzo, Michael; Gonzalez, Felipe; Porras, Kevin; Douglas, Simone; Avila, Marcel; Yoo, Sonia H.; Ziebarth, Noël M.
Abstract: The purpose of this study was to evaluate elasticity and viscoelasticity in the anterior and deeper stromal regions of the cornea after cross linking with three different protocols using atomic force microscopy (AFM) through indentation. A total of 40 porcine corneas were used in this study and were divided into 4 groups (10 corneas per group): control (no treatment), Dresden (corneal epithelial debridement, riboflavin pretreatment for 30 min and a 3mw/cm 2 for 30 min UVA irradiation), accelerated (corneal epithelial debridement, riboflavin pretreatment for 30 min and a 30mw/cm 2 for 3 min UVA irradiation), and genipin (corneal epithelial debridement and submersion of anterior surface in a 1% genipin solution for 4 h). Elasticity and viscoelasticity were quantified using AFM through indentation for all corneas, for the anterior stroma and at a depth of 200 μm. For the control, Dresden, accelerated, and genipin groups, respectively, the average Young's modulus for the anterior stromal region was 0.60 ± 0.58 MPa, 1.58 ± 1.04 MPa, 0.86 ± 0.46 MPa, and 1.71 ± 0.51 MPa; the average for the 200 μm stromal depth was 0.08 ± 0.06 MPa, 0.08 ± 0.04 MPa, 0.08 ± 0.04 MPa, and 0.06 ± 0.01 MPa. Corneas crosslinked with the Dresden protocol and genipin were significantly stiffer than controls (p < 0.05) in the anterior region only. For the control, Dresden, Accelerated, and genipin groups, respectively, the average calculated apparent viscosity for the anterior stroma was 88.2 ± 43.7 kPa-s, 8.3 ± 7.1 kPa-s, 8.1 ± 2.3 kPa-s, and 9.5 ± 3.8 kPa-s; the average for the 200 μm stromal depth was 35.0 ± 3.7 kPa-s, 49.6 ± 35.1 kPa-s, 42.4 ± 17.6 kPa-s, and 41.8 ± 37.6 kPa-s. All crosslinking protocols resulted in a decrease in viscosity in the anterior region only (p < 0.05). The effects of cross-linking seem to be limited to the anterior corneal stroma and do not extend to the deeper stromal region. Additionally, the Dresden and genipin protocols seem to produce a stiffer anterior corneal stroma when compared to the accelerated protocol. Highlights: Cornea stiffness was quantified after crosslinking with three different protocols. The traditional Dresden protocol was more effective than an accelerated protocol. The chemical crosslinker genipin significantly increased corneal stiffness. Crosslinking effects are limited to the anterior corneal stroma.